Effect of heat treatment on cracking and strength of carbon/carbon composites with smooth laminar pyrocarbon matrix. (5th October 2016) - Xia, Lihong; Huang, Boyun; Zhang, Fuqin; Liu, Zuming; Chen, Tengfei
Abstract: Carbon fiber preforms were pre-heat treated at 2100 °C and then filled with smooth laminar (SL) pyrocarbon matrix by isothermal chemical vapor infiltration. The microstructure and flexural properties of carbon/carbon (C/C) composites after heat treatment from 1800 to 2500 °C were investigated. The microstructure investigation indicated that heat treatment did not affect the extinction angle, but resulted in distinct interfacial cracks and concentric cracks in the SL pyrocarbon. Three-point bending tests revealed that the flexural strength of the C/C composites decreased rapidly from 221 to 108 MPa after treated at 2100 °C. This can be explained that the multiple interfacial debonding and concentric cracks lead to poor stress transfer capabilities and high stress concentration. The flexural strength increased back to 126 MPa when the composites were heat treated under a higher temperature at 2500 °C. This phenomenon was attributed to cracks bridging in the debonding region and the thin high-textured layer at the fiber-matrix interface. Graphical abstract: Highlights: After heat treated, distinct interfacial cracks and concentric cracks appeared in the C/C composites. Theoretical calculations of thermal stress and strain were conducted via a simplified mathematical model. The flexural strength first decreased and then increased at the HTT of 2100 °C. The strength evolution is influenced by the combined effects of cracks and the texture degree of pyrocarbon matrix.